Incidence, risk factors and outcomes of AKI among trauma patients in a tertiary hospital in south-east, Nigeria - Chinedu O. Udeze; Monday U. Nwobodo; Olaronke F. Afolabi; Chinaka Ifeanyi; Onyinye J. Nwikwu; Anthony C. Agbo; Christiana Ologwu; Ngozi A. Ifebunandu; Ifeoma I. Ulasi (BMC Nephrology)
Abstract Background Acute kidney injury is a preventable and treatable complication of trauma-related injuries associated with increased mortality. Data on the burden and predisposing factors to the development of AKI following trauma are lacking in our environment. This study aims to evaluate the incidence, predisposing risk factors, and short-term outcomes of AKI in trauma patients seen at the Accident and Emergency Unit of Alex Ekwueme Federal University Teaching Hospital Abakaliki, Nigeria. Methods The study was a hospital-based cohort study of trauma patients. Consenting patients presenting after a trauma-related event were enrolled. Socio-demographic data, the time of the incident, the time of presentation to the hospital, the nature and extent of injuries, and the treatment received were recorded. Blood was taken at specified intervals for haemoglobin, white blood cell count, serum urea, and creatinine estimation. AKI was defined based on the Kidney Disease: Improving Global Outcomes guidelines. Multivariate logistic regression analysis was applied to determine independent risk factors for AKI in trauma patients. Results 186 trauma patients participated; 83.3% were males. The patients’ mean age was 35.3 (± 11.1) years, and most were traders (31.7%). The commonest mechanism of trauma was road traffic accidents (62.9%). The incidence of AKI in this study was 27 (14.5%). Multivariate logistic regression analysis showed that the development of AKI was independently associated with injuries complicated by fractures and longer hospital stay. The 30-day outcome was: 26 (96.3%) recovered fully, and 1 (3.7%) had AKI requiring renal replacement therapy, with no in-hospital mortality. Conclusion AKI is a frequent complication of trauma, and trauma patients presenting with fractures and have prolonged hospital stay require closer monitoring and care.